Systematic review: the effects of long‐term proton pump inhibitor use on serum gastrin levels and gastric histology. Issue 6 (16th July 2015) - Lundell, L.; Vieth, M.; Gibson, F.; Nagy, P.; Kahrilas, P. J.
Summary Background Proton pump inhibitors (PPIs) have a well‐established safety profile. However, concerns have been raised about a potential relationship between PPI‐induced hypergastrinaemia and the development of enterochromaffin‐like (ECL) cell hyperplasia, neuroendocrine tumours and gastric cancer during long‐term therapy. Aim To review the effects of long‐term PPI use on serum gastrin levels and gastric histopathology. Methods A systematic literature search was conducted in PubMed on 21 April 2015 to identify studies reporting the effects of long‐term (defined as >3 years) PPI use on gastrin levels and gastric histopathology. Results A total of 16 studies (1920 patients) met the inclusion criteria. During long‐term PPI therapy, mean gastrin levels rose to one to three times the upper limit of the normal range (~100 pg/mL), and an increased prevalence of ECL cell hyperplasia was observed (+7.8–52.0%). Helicobacter pylori‐positive patients had a significantly increased risk of developing ECL linear/micronodular hyperplasia compared with H. pylori‐negative patients [OR: 2.45 (95% CI: 1.47–4.10), P = 0.0006]; however, no evidence of neoplastic changes was found. The risk of corpus atrophy was markedly higher in H. pylori‐positive patients than in H. pylori‐negative patients [OR: 11.45 (95% CI: 6.25–20.99), P < 0.00001]. Not a single case of gastric adenocarcinoma was found. Conclusions Long‐term PPI therapy induced moderate hypergastrinaemia in most patients and an increased prevalence of ECL cell hyperplasia. H. pylori‐positive patients receiving long‐term PPI therapy were exposed to a higher risk of corpus atrophy than H. pylori‐negative patients. No neuroendocrine tumours or gastric cancers were found.